Studies on Alkyd Cross Linkable Acrylic Hybrid Emulsion for Coating Application (Global Journal of Science Frontier Research, 2018)
A series of alkyd with different oil length, acid and hydroxyl value were synthesized and used for cross linkable alkyd-acrylic hybrid emulsion via free radical polymerization using seeded semi continuous emulsion polymerization technique. The efficiency of different alkyds for stabilization during emulsion polymerization as well as emulsion stability and performance were studied. The stabilization of such type of emulsion was due to partial grafting of acrylic onto the unsaturated part of fatty acid in alkyd. The alkyd stabilized acrylic latex film was characterized by FTIR spectroscopy, thermal analysis and SEM study. The performance of such alkyd stabilized acrylic latex was also compared against acrylic emulsion with respect to drying, adhesion, flexibility and water repellency.
Keywords: alkyd cross linkable emulsion; soya bean oil; emulsion polymerization; acid neutralized alkyd dispersion